Empowering teacher’s role for quality use of medicine / Nur Sabiha Md Hussin and Dr. Gurmeet Kaur Surindar Singh - Md Hussin, Nur Sabiha; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
The Know Your Medicine (KYM) programme was introduced in 2009 to support the fourth component of Malaysian National Medicines Policy (Dasar Ubat Nasional), which is "quality use of medicines". The objective mainly stresses ensuring that medicines are used rationally for better health outcomes. Multiple strategies are used to achieve the goals; among them are education, training, and providing accurate medicine information to consumers. Ensuring the quality use of medicines within the population is the responsibility of healthcare providers, including pharmacists. The 2015 National Survey on the Use of Medicine III by Malaysian Consumers (NSUM III) reported that knowledge about the quality use of medicine is still lacking, despite the ‘Know Your Medicine’ programme having been implemented for six years since its initiation. Thus, a more rigorous effort is needed to increase awareness about the programme's existence. It is essential to promote this programme in every sector possible, including education.